Developmental Changes in the ECG of a Hamster Model of Muscular Dystrophy and Heart Failure - Hampton, Thomas G.; Kale, Ajit; McCue, Scott; Bhagavan, Hemmi; VanDongen, Case (Frontiers in Pharmacology, 2012)
Aberrant autonomic signaling is being increasingly recognized as an important symptom in neuromuscular disorders. The delta-sarcoglycan-deficient BIO TO-2 hamster is recognized as a good model for studying mechanistic pathways and sequelae in muscular dystrophy and heart failure, including autonomic nervous system dysfunction. Recent studies using the TO-2 hamster model have provided promising preclinical results demonstrating the efficacy of gene therapy to treat skeletal muscle weakness and heart failure. Methods to accelerate preclinical testing of gene therapy and new drugs for neuromuscular diseases are urgently needed. The purpose of this investigation was to demonstrate a rapid non-invasive screen for characterizing the autonomic nervous system imbalance in dystrophic TO-2 hamsters. Electrocardiograms were recorded non-invasively in conscious 9-month old TO-2 hamsters (n=10) and non-myopathic F1B control hamsters (n=10). Heart rate was higher in TO-2 hamsters than controls (453 ± 12 bpm vs. 311 ± 25 bpm, P<0.01). Time domain heart rate variability, an index of parasympathetic tone, was lower in TO-2 hamsters (12.2 ± 3.7 bpm vs. 38.2 ± 6.8, P<0.05), as was the coefficient of variance of the RR interval (2.8 ± 0.9 % vs. 16.2 ± 3.4 %, P<0.05) compared to control hamsters. Power spectral analysis demonstrated reduced high frequency and low frequency contributions, indicating autonomic imbalance with increased sympathetic tone and decreased parasympathetic tone in dystrophic TO-2 hamsters. Similar observations in newborn hamsters indicate autonomic nervous dysfunction may occur quite early in life in neuromuscular diseases. Our findings of autonomic abnormalities in newborn hamsters with a mutation in the delta-sarcoglycan gene suggest approaches to correct modulation of the heart rate as prevention or therapy for muscular dystrophies.